Historic Socio-Scientific Interaction in Relationship between Cancer and Environment- As Facts and Fiction - Ghosh , Ilora (Socio-Scientific Interaction in Diabetes and Cancer and Its Management, 2023)
As we stride into 21st century, our spectrum of disease has changed to more chronic disease, while cancer has assumed an epidemic in society. Irrespective of age or health, exposure to pollutants as well as genetics can induce cancer risk. Developing the concept of social science in view of cancer it can be seen as a revolt among a group of cells that do not follow the social contract in the cell community to forgo constant cell division in order to contribute to a greater goal of individual fitness. If we want to understand, cancer is a social phenomenon, concentrating on what energies within a single cell, it is insufficient to attack many of the fundamental mechanisms that support cancer's spread. Although it is useful to detect as many mutations of cancer as possible, what is also needed is to understand how many signalling pathways proteins empower each other, and how they exploit the functions of the normal cells in their neighborhood. Cancer therapy has always been driven by the eradication of proliferating cancer cells through surgical removal or inducing programmed cell death through chemotherapeutic, targeted molecule, or radiation treatment. Although localized tumors can be cured yet systemic therapy virtually always fails to cure metastatic disease as cancer cells appear to develop intrinsic or adaptive resistance strategies i.e. “tumor cell heterogeneity.” So, fields such as physics, computational medicine, phytocomponents, complexity agent-based modeling, sociology, and ecology all have the capacity to drive new insights into cancer biology.